(untitled) (Window of Public Health Journal, 2026)
Work fatigue is a condition characterized by feelings of tiredness that can reduce activity and motivation, potentially affecting a person’s ability to work. This study aims to determine the factors associated with work fatigue among junior doctors (koas) at Ibnu Sina Hospital YW-UMI Makassar. This study used a quantitative, cross-sectional design. The study population was all 172 junior doctors at Ibnu Sina Hospital YW-UMI Makassar. A sample of 120 respondents was obtained using simple random sampling. Data analysis was performed using the chi-square test to assess relationships among variables. The results showed that length of work (p = 0.001), sleep quality (p = 0.041), workload (p = 0.000), and work stress (p = 0.000) were related to the level of work fatigue. Meanwhile, there was no relationship between work shifts and work fatigue (p = 0.863). This study concludes that work length, sleep quality, workload, and work stress are related to the level of work fatigue among junior doctors. Therefore, it is recommended for young doctors to regulate their lifestyle and time management to reduce fatigue at work.